2018
DOI: 10.1186/s13148-018-0447-6
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of DNA damage repair (DDR) genes in human tumor entities: RBBP8/CtIP is almost exclusively methylated in bladder cancer

Abstract: BackgroundGenome-wide studies identified pan-cancer genes and shared biological networks affected by epigenetic dysregulation among diverse tumor entities. Here, we systematically screened for hypermethylation of DNA damage repair (DDR) genes in a comprehensive candidate-approach and exemplarily identify and validate candidate DDR genes as targets of epigenetic inactivation unique to bladder cancer (BLCA), which may serve as non-invasive biomarkers.MethodsGenome-wide DNA methylation datasets (2755 CpG probes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…Soria-Bretones et al (2013) observed decreased or no expression of RBBP8 in paraffinembedded breast cancer biopsy tissues from high-grade breast cancer and nodal metastases that were acquired during tumor removal surgery (Soria-Bretones et al, 2013). The research group led by Rose et al suggested that RBBP8 was significantly hypermethylated in bladder cancer (BLCA) and was associated with more prolonged overall survival, and they indicated that it may be used as a complementary marker for the detection of BLCA in urine (Mijnes et al, 2018). Miao et al (2019) reported that the downregulation of the long noncoding RNA (lncRNA) cancer susceptibility candidate 2 (CASC2, enhanced tumor development, increased miR-18a-5p levels, and reduced the expression of RBBP8 in nasopharyngeal carcinoma (NPC).…”
Section: Discussionmentioning
confidence: 99%
“…Soria-Bretones et al (2013) observed decreased or no expression of RBBP8 in paraffinembedded breast cancer biopsy tissues from high-grade breast cancer and nodal metastases that were acquired during tumor removal surgery (Soria-Bretones et al, 2013). The research group led by Rose et al suggested that RBBP8 was significantly hypermethylated in bladder cancer (BLCA) and was associated with more prolonged overall survival, and they indicated that it may be used as a complementary marker for the detection of BLCA in urine (Mijnes et al, 2018). Miao et al (2019) reported that the downregulation of the long noncoding RNA (lncRNA) cancer susceptibility candidate 2 (CASC2, enhanced tumor development, increased miR-18a-5p levels, and reduced the expression of RBBP8 in nasopharyngeal carcinoma (NPC).…”
Section: Discussionmentioning
confidence: 99%
“…Infinium HumanMethylation450 BeadChip data (level 2) and RNASeqV2 data (level 3) of the tumor and normal tissue samples were obtained from the TCGA data portal [30] and analyzed, as previously described [43].…”
Section: Tcga Blca Data Setmentioning
confidence: 99%
“…OS was measured from surgery until death and it was censored for patients alive without evidence of death at the last follow-up date. The receiver operating characteristics (ROC) curves and AUC values were calculated to assess the biomarker performance of ECRG4 and ITIH5 methylation similar to our previous report [43]. The ROC curves of combined biomarkers were based on the binary logistic regression model using the probability as test variable.…”
Section: Statistical Data Acquisitionmentioning
confidence: 99%
“…Investigation found RBBP8 genes was associated with sporadic brain arteriovenous malformations [19]. Advanced invasive bladder cancer was associated with the deletion of nuclear RBBP8 protein [20]. Deletion of the RBBP8 gene was associated with significantly worse prognosis in ovarian cancer [21].…”
Section: Introductionmentioning
confidence: 99%